Paternal or maternal history of hypertension is more important in increasing the risk of hypertension inoffspring? - Khosravi, Alireza; Gharipour, Mojgan; Behjati, Mohaddeseh; Sadeghi, Masoumeh; Nezafati, Pouja; Talaie, Mohammad; Shirani, Shahin; Jozan, Mahnaz (Acta Biomedica Atenei Parmensis, 2016)
Background: Along with tripartiteclose relationship of socioeconomic level, smoking, and prevalence of hypertension, the present study aimed to assess the relationship between socioeconomic status (SES) and hypertension based on habitual smoking in Iranian population. Methods: The present study analyzed the individuals subsample consisted of 9623 subjects, out of all people resident in Isfahan province in Iran of the wave of the Isfahan Heart Health Project (IHHP) in three cities in Iran: Isfahan, Najafabad and Arak. Systolic and diastolic blood pressures were measured in supine position using an automated blood pressure monitor. Smokers were defined as persons who were smoked prior to the survey and never smokers were defined as a person who had never smoked. Results: Those individuals who experienced cigarette smoking, SES class was significantly lower in hypertensive patients compared with normotensive subject so 7.8% of hypertensive patients and 92.2% of normotensive ones classified in SES class IV (p<0.001). Univariate analysis showed hypertension was related to lower SES class when compared with normotension status in both smoker and nonsmoker groups (p<0.001). In stepwise logistic regression models adjusting sex, age, global dietary index and leisure time physical activity, hypertension could be predicted by lower SES in nonsmoker group, while this predictive role for SES could not be reveal in smoker group. Conclusion: The significant SES-smoking association may determinate in the increasing blood pressure even adjusted for other covariates such as demographics as well as dietary behaviors and leisure time physical activity.